Effects of biochar amendment in two soils on greenhouse gas emissions and crop production - Wang, Jinyang; Pan, Xiaojian; Liu, Yinglie; Zhang, Xiaolin; Xiong, Zhengqin (Plant and soil, 2012)
Background Worldwide, there is an increasing interest in using biochar in agriculture to help mitigate global warming and improve crop productivity. Methods The effects of biochar on greenhouse gas (GHG) emissions and rice and wheat yields were assessed using outdoor pot experiments in two different soils (upland soil vs. paddy soil) and an aerobic incubation experiment in the paddy soil. Results Biochar addition to the upland soil increased methane (CH4) emissions by 37 % during the rice season, while it had no effect on CH4 emissions during the wheat season. Biochar amendment decreased nitrous oxide (N2O) emissions up to 54 % and 53 % during the rice and wheat seasons, respectively, but had no effect on the ecosystem respiration in either crop season. In the aerobic incubation experiment, biochar addition significantly decreased N2O emissions and increased carbon dioxide (CO2) emissions from the paddy soil (P<0.01) without urea nitrogen. Biochar addition increased grain yield and biomass if applied with nitrogen fertilizer. Averaged over the two soils, biochar amendments increased the production of rice and wheat by 12 % and 17 %, respectively, and these increases can be partly attributed to the increases in soil nitrate retention. Conclusions Our results demonstrated that although biochar increased the global warming potential at high nitrogen fertilizer application, biochar incorporation significantly decreased N2O emissions while promoting crop production.